Aspek Etika Medikolegal Atas Penggunaan Artificial Intelligence Pada Praktik Kedokteran Bidang Radiologi - Alam, Chessa Rahadi; Hehalatu, Alga; Amarantha, Dessy; Jalaludin, Jalaludin; Lestari, Ayang Prima; Aristiara, Adiwirya; Prayuti, Yuyut (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to determine ethicomedicolegal aspects of the Use of Artificial Intelligence in the practice of radiology medicine. According to Health Law No. 17 of 2023 Article 273 paragraph 1, it is explained that medical personnel and health workers in carrying out their practices have the right to receive legal protection as long as they carry out their duties in accordance with professional standards, professional service standards, operational procedure standards, and professional ethics, as well as patient health needs. This type of research is descriptive analytical, namely describing the applicable laws and regulations related to the ethicomedicolegal aspects. The results of the study indicate that legal protection for health workers in the use of Artificial Intelligence is still lacking, so additional studies are needed. The need for strong regulations such as training and delegation of authority in accordance with applicable health laws to protect health workers from unwanted things.